Money now, Money later: linking time discounting and criminal convictions in the Cambridge study in delinquent development - Piquero, Alex R. (International journal of offender therapy and comparative criminology, 2018)
Two prominent criminological theories offer time discounting, or the preference for an immediate reward over a later one, as a central part of understanding involvement in criminal activity. Yet, there exist only a few studies investigating this issue, and they are limited in a few respects. The current study extends prior work in this area by using multiple measures of time discounting collected at three different periods of the life course to examine the link to criminal offending into late middle adulthood in the Cambridge Study in Delinquent Development. Results show that greater time discounting is positively related to a higher number of criminal convictions by late middle adulthood, and this effect remains after controlling for early life-course individual and environmental risk in a multivariate framework. Study limitations and implications are also discussed.